2022
DOI: 10.1016/j.jhsg.2021.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Distal Biceps Tendon Rupture Videos on YouTube: An Analysis of Video Content and Quality

Abstract: Purpose: Our purpose was to analyze the content and quality of YouTube videos related to distal biceps tendon (DBT) ruptures and repair. We aimed to compare differences between academic and nonacademic video sources. Methods: The most popular YouTube videos related to DBT injuries were compiled and analyzed according to source. Viewing characteristics were determined for each video. Video content and quality were assessed by 2 reviewers and analyzed according to the Journal of the American Medical Association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
5
4
Order By: Relevance
“…24 It is also possible that surgical technique videos or those uploaded for surgeon training may have low quality and reliability points according to patients as they are not the target mass. 25 The high number of surgical videos in this study may have been a reason for the insufficiency on the subject of patient education.…”
Section: Discussionmentioning
confidence: 95%
“…24 It is also possible that surgical technique videos or those uploaded for surgeon training may have low quality and reliability points according to patients as they are not the target mass. 25 The high number of surgical videos in this study may have been a reason for the insufficiency on the subject of patient education.…”
Section: Discussionmentioning
confidence: 95%
“…According to a recent YouTube analysis of distal biceps tendon rupture [ 9 ], the videos submitted by academic sources did not appear to be of a higher caliber than those uploaded by non-academic sources. Our results differ from those of Brian et al as tendon repair surgery videos posted by academic sources received higher content or quality ratings than those from non-academic sources [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we had to be rigorous in our inclusion criteria to ensure that videos were of sufficient quality to perform accurate analysis. Indeed, in a study looking at quality of YouTube videos in relation to DBTR, Foster et al 14 concluded that the overall quality was poor, although the scope of their study was to analyze content rather than visual clarity. They also reported that videos posted by academic and non-academic sources were of similar poor standard with reference to content and information.…”
Section: Discussionmentioning
confidence: 99%